2013
DOI: 10.1016/j.apsusc.2013.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamic simulation of binary ZrxCu100−x metallic glass thin film growth

Abstract: In this work, we employed classical molecular dynamics simulations model to study Zr x Cu 100-x (3 ≤ x ≤ 95) metallic glass films deposited on a silicon (100) substrate. Input data were chosen to fit with the experimental operating conditions of a magnetron sputtering deposition system. The growth evolution is monitored with variable compositions of the incoming atom vapor. The Zr-Zr, Cu-Cu and Zr-Cu interactions are modeled with the Embedded Atom Method (EAM), the Si-Si interaction with Tersoff potential, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…We use the modified Thompson formula (detailed in Supplementary) to calculate the mean kinetic energy [38] of the incoming Zr and Cu atoms. We examine three different experimental conditions (Table 1).…”
Section: Models and Methodsmentioning
confidence: 99%
“…We use the modified Thompson formula (detailed in Supplementary) to calculate the mean kinetic energy [38] of the incoming Zr and Cu atoms. We examine three different experimental conditions (Table 1).…”
Section: Models and Methodsmentioning
confidence: 99%
“…28 29 In a recent study Xie et al also fabricated glassy films of Zr x Cu 100−x (20 < x < 80) alloys by magnetron sputtering. 30 Almyras et al have studied the deposition mechanism and the formation of glassy thin films in Cu-Zr system. They found that simultaneous deposition of both metals leads to formation of an amorphous film whereas sequential deposition results in crystalline films.…”
Section: Articlementioning
confidence: 99%
“…It is known that with increasing Zr content the position of the first halo in XRD patterns 30 and the crystallization temperature 49 50 of Cu x Zr 100−x glassy films is generally shifted to lower diffraction angles and temperatures, respectively. As shown in Figure 4, the strong peak of the underlying amorphous BK7 substrate dominates the range of diffraction angles ( = 10-20 degrees) in our experiments where the first halo of the Zr-rich phase would be located.…”
Section: Materials Expressmentioning
confidence: 99%
“…The microstructure of the thin film also depends on its chemical composition since the glass forming ability is compositiondependent. For example, co-sputtered binary Zr x Cu 100-x thin films [21] containing more than 80 at. % Zr or Cu are crystalline while for intermediate compositions they exhibit a low order phase (i.e., amorphous) according to both experimental results and molecular dynamic simulations.…”
Section: Accepted Manuscriptmentioning
confidence: 99%